Ganges Coastal Zone Issue Briefs - CGIAR Challenge Program on Water and Food (2014)
A series of five issue briefs based on CPWF research on agricultural and aquacultural production and food security in the Ganges coastal zone. The brief topics are: water smart communities; agricultural production and drainage; governance by small water management units; community approach to water management; and improved agriculture and aquaculture cropping systems.